False nostalgia : the Marcos "golden age" myths and how to debunk them - Punongbayan, JC (Makati City : ADMU Press, 2023)
This book is going to be perhaps the most lethal weapon in the arsenal against the so-far partially successful attempts (thanks to social media) to tout the 20-year Marcos era (January 1966 to February 1986) as a (3z(Bgolden age(3y (Bin Philippine history. Specifically, JC Punongbayan relentlessly examines every one of 43 claims that have been made regarding that period$1 (Bfrom the faintly ridiculous (that Imelda Marcos did not use public funds to build her (3z(Bbopis(3y (Bhospitals) to the utterly insane (that nobody was poor during the Marcos regime). And he debunks every one of them with a mountain of data and past studies, all footnoted, referenced, and acknowledged so anyone can check and see for themselves the accuracy of JC$1 (Bs rebuttals. The joy of it is that he combines seven years of scholarly research with simple, clear, compelling writing. Bravo!s
PART 1. Carefree Utopia -- PART 2. Crisis Mismanagement -- PART 3. Crazy Rich Filipinos.
Includes bibliographical references.
Keywords: MARCOS, FERDINAND E; PHILIPPINES, PRESIDENT (1965-1986 : MARCOS); PHILIPPINES -- POLITICS AND GOVERNMENT -- 1965-1986